Regional culturemes in selected textbooks for teaching Polish as a foreign language - Zwolińska, Paulina (Activation-innovation-inspiration in (glotto) didactics, 2022)
Culturemes are carriers of the traditions and beliefs of a community, therefore they are symbols of specific cities, regions and countries. The article presents an analysis of three general course textbooks for teaching Polish as a foreign language at A1 level in terms of the presence of regional culturemes in them. I assumed that regional culturemes should be understood as elements characteristic for individual areas of Poland and sometimes for the whole country at the same time. The extracted local culturemes belong, first of all, to high, popular and folk culture. Their selection and placement in books allows us to conclude which lexemes, according to the authors, should be learned by foreigners.